Story/Time : The Life of an Idea - Jones, Bill T. (Book collections on Project MUSE., 2014)
In this ceaselessly questioning book, acclaimed African American dancer, choreographer, and director Bill T. Jones reflects on his art and life as he describes the genesis of Story/Time, a recent dance work produced by his company and inspired by the modernist composer and performer John Cage. Presenting personally revealing stories, richly illustrated with striking color photographs of the work's original stage production, and featuring a beautiful, large-format design, the book is a work of art in itself. Like the dance work, Story/Time the book is filled with telling.